2003
DOI: 10.1111/j.1651-2227.2003.tb02518.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of cirrhotic regenerative liver nodules upon NTBC treatment in a child with tyrosinaemia type I

Abstract: In a male patient with hereditary tyrosinaemia type I (HTI), NTBC [2‐(2‐nitro‐4‐trifluoro‐methylbenzoyl)‐1,3‐cyclohexandion] treatment and a diet low in phenylalanine and tyrosine were started at the age of 4 wk. At the recommended average dosage (1 mg kg−1), liver failure improved transiently. After 4 mo of treatment, with increased body weight, the dose had decreased to 0.7 mg kg−1, and diffuse cirrhotic changes in liver parenchyma and multiple nodules were visualized by ultrasonography. Multiple nodules in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…The third patient was treated very late and had to be transplanted because of cirrhosis. Some cirrhotic lesions may be reversible upon NTBC treatment (Crone et al 2003), but in that reported case treatment had started at 4 weeks of age, which probably explains such reversibility. In our series, cirrhosis was persistent in 6 patients.…”
Section: Discussionmentioning
confidence: 88%
“…The third patient was treated very late and had to be transplanted because of cirrhosis. Some cirrhotic lesions may be reversible upon NTBC treatment (Crone et al 2003), but in that reported case treatment had started at 4 weeks of age, which probably explains such reversibility. In our series, cirrhosis was persistent in 6 patients.…”
Section: Discussionmentioning
confidence: 88%
“…Increase of AFP may be a reflection of insufficient metabolic control; however, further examination to exclude hepatocellular carcinoma (HCC) is usually warranted. [20,21] Patients with persistently high levels of AFP are probably at risk of developing cancer as already reported. [22] Another long-term hepatic complication of HT1 is cirrhosis.…”
mentioning
confidence: 79%
“…La otra paciente comenzó el tratamiento a los 10 años, teniendo sintomatología desde los 8 meses de vida. En la publicación de Holme 12 de los 101 pacientes que recibieron NTBC antes de los 2 años, ninguno desarrolló hepatocarcinoma a los 2 años de tratamiento, lo que concuerda con lo descrito por otros autores 14,15 y lo observado en este estudio.…”
Section: Discussionunclassified